The Affect Of Profitability, Leverage And Company Size On Enterprise Value In Financial Industry Section Company In BEI 2021-2022 - Mutiara, Ode; Diani, Nurwidiani; Nurwidiani, Nurwidiani; Murhan, Muchriana (Jurnal Penelitian IPTEKS, 2024)
This study aims to test the effect of profitability, leverage, and corporate size on corporate value. The research population includes all financial sector companies registered with the BEI for 2021-2022. This study sample was obtained using the purposive sampling method, in which only 32 financial sector companies registered with the BEI met all criteria, so 64 data were used as research samples. This study used multiple regression models to test the effect of each independent variable on the dependent variable. The results of this study show that corporate profitability, leverage, and size partially affect corporate value.